A Critical Analysis of Building Metaphors in The Boycott Israel Discourse in The Al Jazeera Arabic Online Newspaper - Fathurrohim, Ilham Hanif; Nur, Tajudin; Krisnawati, Ekaning (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
Since the ṭūfānu ‘l-ʔaqṣā operation, boycotts against Israel have become increasingly common. This has resulted in a decline in revenue for Israeli companies in Muslim countries, which also includes Arab countries. Al Jazeera as the largest media outlet in Arab countries has a role in shaping the Arab public's perception of the boycott. One feature that is widely used by the media to persuade its readers is metaphor. One of the most popular metaphors used in various domains of human life is the building metaphor. This research aims to analyze the conceptual metaphor of building, as well as reveal the ideology behind it using a critical metaphor analysis approach. Data were obtained from the boycott discourse in Al Jazeera Arabic Online Newspaper since the ṭūfānu ‘l-ʔaqṣā operation until October 2024. The results show that all building lexemes evaluate the boycott positively by seeing it as a form of resistance against Israel. This is done by highlighting the complexity of Israeli capitalism, the strength of the boycott, the impact of the boycott on Israel, the positive impact of the boycott on the local economy, and the support that Palestine still needs. All of these metaphors are based on the ideology of resistance, which emphasizes the importance of resistance to all forms of oppression. This shows that Al Jazeera is in favor of Palestine by supporting resistance against Israel through boycotts. This findings support previous research that building metaphors are often used in many domains of human life, including the political and economic domains in this boycott phenomenon.